Temperature control on multiple electrical appliance - Jemat, Fairuz Firdausi; Kahardy, Syafiq (2016)
This project is created to save time and energy. Its significance in today’s world is immense when people don’t have to unnecessarily waste their time in operating the appliances by being near to the appliance. They can operate it while they’re engrossed in whatever task they’re doing and don’t have to bother leaving it in between. Especially those who suffer from physical problems, age and laziness. For example, operating conventional wall switches is difficult for elderly physically handicapped people. With this project, we can reduce human effort to use home appliances physically by using automated control to control the home appliance. We use an Arduino Rev3 and LM 35 temperature sensor to operate this system. The advantage is that it can be operated automatically without the person to physically move to switch on the device. It can be used in the case of a number of devices and applications such as fan, heater, air conditioning, curtains and roof shading.